Unique features of Entamoeba histolytica glycerophospholipid metabolism; has the E. histolytica lipid metabolism network evolved through gene loss and gain to enable parasitic life cycle adaptation? - Fumika Mi-ichi; Hiroshi Tsugawa; Hiroki Yoshida; Makoto Arita (mSphere, 2023)
ABSTRACT Entamoeba histolytica, a protozoan parasite, causes amoebiasis, which is a global public health problem. During the life cycle of this parasite, the properties of the cell membrane are changed markedly. To clarify the mechanism of membrane lipid changes, we exploited state-of-the-art untargeted lipidomic analysis, and atypical features of glycerophospholipids, lysoglycerophospholipids, and sphingolipids were observed compared with human equivalents. Here, we overview an entire E. histolytica glycerophospholipid metabolic pathway based on re-evaluated whole lipidome and genome along with the results of metabolic labeling experiments. We also discuss whether the E. histolytica lipid metabolism network, including the glycerophospholipid metabolic pathway, has unique features necessary for parasitic life cycle adaptation through gene loss and/or gain, and raise important questions involving biochemistry, molecular cell biology, and physiology underlying this network. Answering these questions will advance the understanding of Entamoeba physiology and will provide potential targets to develop new anti-amoebiasis drugs.